An essay on relational analysis of relational sociology - Kasapoglu, Aytul (Edelweiss Applied Science and Technology, 2025)
In recent years, examining social problems such as health, education, environment, poverty, migration, disaster, all kinds of discrimination and inequalities in a relational and intersectional manner has become increasingly preferred. Especially sociologists find the essentialist approach of classical mainstream sociology based on dualities such as traditional-modern, structure and individual inadequate for themselves. In the age of uncertainties and complexities, old views that assumed a human-centered, deterministic and linear imposed by classical or traditional sociological theories have begun to be criticized. In this context, there has been a need to renew the definition of social in a way that includes not only humans but also the beings in our natural environment such as plants, animals and soil. Since it is not appropriate and possible to call this perspective, which finds all dualities such as human-nonhuman, structure-individual, traditional-modern, time-space, macro-micro artificial and prefers process-based analyses, as a new paradigm due to its nature, it is preferred to call it a way of doing sociology. In this original research paper, first the historical development of relational sociology in the world and its differences from classical sociology are revealed. Then, relational sociological studies conducted in Turkey are examined. In fact, within the framework of the article, some predictions are tried to be made about the future of relational sociology based on its current situation. The originality of the article stems from the effort to conduct this systematic review in accordance with relational sociological principles.